Features of organizing an elective course on non-standard problems for pupils of grades 5-6 (Journal of Educational Sciences, 2022)
Currently, one of the relevant topics is the inclusion of elective courses in the school curriculum. The education of creative potential, the development of logical thinking, a certain contribution to hardening will lead to a significant result. This article will focus on the elective course program for solving non-standard tasks for grades 5-6 of secondary school. The introduction provides some information about the logical problem. At the same time, the definition of a non-standard report is given. Information about the elective course has been announced. In addition, approaches to the organization of an elective course are provided. About twenty topics have been selected for the organization of this elective course. The topics listed are listed according to the number of hours. We are talking about the logical sequence of the received topics. We are talking about the fact that it is compiled in a logical sequence, based on the shedule plan of the secondary school and comparison on the topics covered.In particular, importance is also attached to the sequential arrangement of algebraic and geometric problems. In order to reveal the meaning of the chosen topic, reports on each topic are provided. The solution of all problems is shown. In the final part, we are talking about preparing pupils for the release of a series of reports on these topics. In the future, it is planned to issue a specific methodological manual for the elective course.Keywords: non-standard problems, elective course, logic, secondary school, methodical manual,  problem book.